Fundamentals of Electronics 1 : Electronic Components and Elementary Functions. - Muret, Pierre (John Wiley & Sons, Incorporated, 2017)
Electronics has undergone important and rapid developments over the last 60 years, which have generated a large range of theoretical and practical notions. This book presents a comprehensive treatise of the evolution of electronics for the reader to grasp both fundamental concepts and the associated practical applications through examples and exercises. This first volume of the Fundamentals of Electronics series comprises four chapters devoted to elementary devices, i.e. diodes, bipolar junction transistors and related devices, field effect transistors and amplifiers, their electrical models and the basic functions they can achieve. Volumes to come will deal with systems in the continuous time regime, the various aspects of sampling signals and systems using analog (A) and digital (D) treatments, quantized level systems, as well as DA and AD converter principles and realizations.